UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS III A SDN 008 SALO KECAMATAN SALO KABUPATEN KAMPAR TP 2011-2012 - Dewi Sri Yuliati; Zuhri D; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
This research is a classroom actionresearch aims to improve and enhancethe learning outcomes math. Implementation of the research done in class IIIASDN 008 Salo Kecamatan Salo, were 22 students the first semester of 2012. Theresearch was conducted by two cycles, each cycle performed three learningsessions and one tests. Quantitative data obtained through testing for learningoutcomes and qualitativedata abaut the activities of teachers and students throughobservation sheet. Quantitative analysis of the result of the analysis showed thatthe average score of the class IIIA SDN 008 Salo Kecamatan Salo has increased.Quantitative an increase in motivation, interests, and activities of students andteachers in learning of operation of fraction number math with type cooperativelearning STAD. Based on the results of this study concluded that with theimplementation of cooperative learning model type STAD can improve studentlearning outcomes math class IIIA SDN 008 Salo Kecamatan Salo.Key word: learning outcomes, learning cooperative type STAD.